Foundations of Early Childhood : Principles and Practice - Mukherji, Penny; Dryden, Louise (SAGE Publications Ltd, 2014)
Introducing the major concepts and theories of early years care and education, this text helps you examine topics in depth, using level appropriate tasks and further reading, as well as supporting your development of key academic skills.